O semblante da clínica dialítica no contexto da promoção da saúde: reflexões dos profissionais sobre sua práxis - Dias, Maria Socorro de Araújo (2005)
Studies that focus health care on medicai practice reveal that the dominant professional model is the complex whole ofthe technological apparatus and legal policy, limiting the area of medicai practice to rehabilitation or cure and as a consequence distancing it from an effective health promoting práxis. This study had the objective of comprehending and analyzing notions about medicai practice that is also a health promoting area from health professionals who work with people with CRI (Chronic Renal Insuffíciency). We examined the condition of the profession on medicai practice and on health promotion. We selected the notion of Medicai Practice for the Citizen (Campos, 2003) during the time that it appeared as a medicai practice capable ofsurpassing care historically determined by the Flexnerian model and integrating it into the Health Promotion network The theoretic-methodological option ofthe study was based on the hermeneutic-dialectic (Minayo, 1999,2002) guided by the qualitative methodology. The survey focused the práxis of health professionals who develop their actions in a dialysis clinic in a hospital referral unit for the northern zone of the State of Ceará, totaling 23 professionals from a medicai and nursing team. For data collection open interviews, documental sources and observations registered in the field diary were used. In dealing with data, understood here as texts, we are enthusiastic about the principie that the texts must be understood in their contexts within the movements suggested by hermeneutic-dialectic - explanaiion, interpretaiion and criticism Faced with the results obtained, we considered that in the dialysis clinic there is the coexistence of an Official Medicai Practice and a Medicai Practice for the Citizen, revealing the surpassing of official discourse on social subjects of this medicai practice about its práxis for a health promoting medicai practice. We point out that this survey offers a reflection that has the potential to contribute towards health professionals and health policies with an objective image of medicai practice expressed by the social subjects ofthe study.